Basaltic material in the main belt: a tale of two (or more) parent bodies?. Issue 2 (14th June 2018) - Ieva, S; Dotto, E; Lazzaro, D; Fulvio, D; Perna, D; Mazzotta Epifani, E; Medeiros, H; Fulchignoni, M
ABSTRACT: The majority of basaltic objects in the main belt are dynamically connected to Vesta, the largest differentiated asteroid known. Others, due to their current orbital parameters, cannot be easily dynamically linked to Vesta. This is particularly true for all the basaltic asteroids located beyond 2.5 au, where lies the 3:1 mean motion resonance with Jupiter. In order to investigate the presence of other V-type asteroids in the middle and outer main belt (MOVs) we started an observational campaign to spectroscopically characterize in the visible range MOV candidates. We observed 18 basaltic candidates from TNG and ESO-NTT between 2015 and 2016. We derived spectral parameters using the same approach adopted in our recent statistical analysis and we compared our data with orbital parameters to look for possible clusters of MOVs in the main belt, symptomatic for a new basaltic family. Our analysis seemed to point out that MOVs show different spectral parameters respect to other basaltic bodies in the main belt, which could account for a diverse mineralogy than Vesta; moreover, some of them belong to the Eos family, suggesting the possibility of another basaltic progenitor. This could have strong repercussions on the temperature gradient present in the early Solar system, and on our current understanding of differentiation processes.